Molecular characterisation of five nematode species (Chromadorida, Selachinematidae) from shelf and upper slope sediments off New Zealand, with description of three new species - Leduc, Daniel; Zhao, Zeng Qi (Zootaxa, 2016)
Limited molecular sequence data are available for selachinematid nematodes, with little or no data from the Southern Hemisphere or habitats beyond the subtidal zone. Here, we provide molecular sequence data for the small subunit (SSU) 18S rDNA gene and D2–D3 region of large subunit (LSU) 28S rDNA gene of three new (Cheironchus haurakiensis n. sp., Halichoanolaimus anisospermus n. sp., and Bendiella longicauda n. sp.) and two known selachinematid species (Pseudocheironchus ingluviosus Leduc, 2013 and Synonchiella rotundicauda Leduc, 2013) from shelf and upper slope environments off northeastern New Zealand. Cheironchus haurakiensis n. sp. is characterised by having a multispiral amphideal fovea with five turns, lateroventral mandibles with central arm curved distally and bearing 4–5 pointed projections, and each palm bearing 4–5 pointed projections, ten precloacal supplements in a 1 + 9 arrangement, spicules 78 µm long, and blunt conical tail with thickened cuticle. Halichoanolaimus anisospermus n. sp. is characterised by having an amphideal fovea with 5-6 turns, anterior portion of buccal cavity with cuticularised rhabdions terminating in three sets of seven pairs of teeth (denticles), with the central pair of each set positioned above the other six, dimorphism in size of sperm cells between anterior and posterior testes, gubernaculum consisting of two detached lateral pieces (crurae) tapering distally, three small precloacal supplements consisting of slightly thickened and raised cuticle, and a conicocylindrical tail with conical portion 32–38% of total tail length. Bendiella longicauda n. sp. is characterised by having two dorsosublateral rows of pores from midbody to level of cloaca, amphideal fovea with 4.5 turns, posterior rhabdions with numerous small denticles, spicules 2.1 cloacal body diameters long, a conicocylindrical tail 13.3 cloacal body diameters long and with conical portion 8% of tail length. Preliminary phylogenetic analyses for the family Selachinematidae do not provide evidence of clustering according to depth (intertidal/subtidal vs shelf/upper slope) or geographical location (New Zealand vs Northern Hemisphere). The number of available Selachinematidae sequences, however, remains limited and comprehensive analyses based on larger number of sequences will be necessary to provide more solid conclusions.